¿Empresas tercerizadoras y trabajadores no registrados?: a propósito de la Casación Laboral 11312-2016-Junín - Guzmán Estrada, Lucía Alejandra (Pontificia Universidad Católica del Perú, 2019)
This article aims to analyze the legal issues identified among the jurisprudential criteria considered to declare the perversion of labour relationships, specifi cally in relation to outsourcing, in the labour Cassation Sentence 11312-2016-Junin, judgement issued by the Second Constitutional and Social Chamber of the Supreme Court of Peru. The author begins the analysis by developing a brief legal frame on outsourcing in Peru to then outline the Cassation Sentence 11312-2016-Junin from the Supreme Court’s case law. Moreover,she analyzes its reasoning and identifi es, criticizes and problematizes two legal issues. Finally, as a conclusion, provides a critical evaluation about the case’s setilement.

El presente artículo tiene como objetivo analizar los problemas jurídicos identificados respecto a los criterios jurisprudenciales empleados para declarar la desnaturalización, en particular ante la figura de la tercerización, a partir de la Casación Laboral 11312-2016 Junín, sentencia emitida por la Segunda Sala Constitucional y Social de la Corte Suprema del Perú. La autora inicia el análisis desarrollando un breve marco jurídico sobre la tercerización de servicios en el Perú para, posteriormente, esbozar los antecedentes de la Casación Laboral 11312-2016-Junín. A continuación, analiza sus fundamentos e identifica, critica y problematiza dos problemas jurídicos. Finalmente, a modo de conclusión, expone un juicio crítico sobre la resolución del caso.
Outsourcing companies and unregistered workers: Apropos of the Sentence 11312-2016-Junin from the Supreme Court
Keywords: Tercerización de servicios; Desnaturalización; Centro de trabajo; Registro; Desplazamiento; https://purl.org/pe-repo/ocde/ford#5.05.01